Pengelolaan Dokumen Digital untuk Meningkatkan Efektivitas Pembelajaran PAUD - Takdir Ali Mukti; Siti Muslikhati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Early Childhood Education (PAUD) Anggrek in Parangtritis Village, in responding to the covid-19 pandemic, has adapted learning for students by carrying out an assignment learning program from home, which is regularly given assignments every week on Mondays. The problem that arises from this learning system is the accumulation of files resulting from student assignments that require storage and management, which is quite inconvenient for teachers. This community service offers and implements a learning document digitization program to address existing problems. This service program is carried out using an institutional approach method, through three main activities, namely objectification in the preparation of digital document management steps; externalization in the form of focus group discussions for managers and related stakeholders; and internalization in the form of coaching for PAUD management trainers and several hamlet cadres. The evaluation results showed a significant increase in the effectiveness of managing learning documents, namely the reduction of files that had to be physically stored by 90% from the amount usually held in the previous PAUD office.